Practices developed by nurses in primary health care in southern Brazil - Beatriz Rosana Gonçalves de Oliveira Toso; Bárbara Izabella Orth; Leticia Becker Vieira; Carlise Rigon Dalla Nora; Daniela Savi Geremia; Ana Valéria Machado Mendonça; Maria Fátima de Sousa (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To understand the practices developed by nurses in primary care in southern Brazil. Method: Qualitative study, with data collection via online interviews, conducted between October 2020 and May 2021, and recorded. 174 nurses from 24 municipalities in southern Brazil participated. Data analysis used inductive thematic analysis. Results: The activity that stood out among nurses was the nurse consultation, for all age groups and health conditions, especially when dealing with chronic disease, prenatal care, attention to women and children, mental health, home visits, and the management of the nursing team and the health unit. Final considerations: This study demonstrated that an excess of responsibilities associated to care and management, added to a lack of balance in the activities common to the team make it difficult for nurses to develop clinical practices.